(untitled) (Letras, 2019)
In a homage volume to John Esten Keller, published in 1980, I presented an essay on a story in the Libro de las bienandanzas e fortunas of Lope García de Salazar of how a dolphin saves the life of the firstborn son of the king of France. According to Salazar, the incident serves to explain the origin of the title dauphin and the name of the province Dauphiné, and also the representation of dolphins on the heraldic arms of the dauphin and his territory. In the essay I declared that I was unaware of any other medieval version of the story. Recently, however, I came across a similar version of the tale in Ferrán Mexía’s Nobiliario vero and also a Portuguese translation of this version in the Tratado Geral de Nobreza, attributed to António Rodrigues, Portugal King of Arms. The three texts are witnesses to a probable French source in common, now lost or unknown.